The Periodontal Benefit of Orthodontic Tooth Movement in a Deep Facial Recession of a Mandibular Incisor - Ivan Pedro Taffarel; Caio Seiti Miyoshi; Ivan Toshio Maruo; Thiago Martins Meira; Orlando Motohiro Tanaka (Hindawi Limited, 2019)
Gingival recession refers to the exposure of the tooth's surface by an apical shift of the gingiva. The aim of this paper is to present a clinical case of an adult patient with a skeletal Class I and clinically deep gingival recession in the mandibular left central incisor. A preadjusted appliance with 0.022 in×0.028 in slot was placed in both arches. Rectangular arches were used, with the addition of root lingual torque, specifically in the left lower central incisor. Class II and vertical intermaxillary elastics were used throughout the active treatment to obtain intercuspation of the posterior teeth. The orthodontic movement with the application of a localized biomechanics system of forces into the mandibular left central incisor delivered good dental and functional occlusion and, mainly, gingival and periodontal health. The follow-up showed stable results with the periodontium within normal limits and an improved occlusal interdigitation.